Pengembangan Multimedia Interaktif Berbasis Visual Tiga Dimensi untuk Pembelajaran Numerasi Anak Tunagrahita - Ayu Kristin Natalia Sinaga; I Ketut Purnamawan; Putu Hendra Suputra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to develop three-dimensional visual-based interactive multimedia to be used as a learning aid for numeracy among children with intellectual disabilities. The study was conducted at the Cahaya Impian Masa Depan (CIMD) Foundation. The research method employed the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The developed multimedia is capable of displaying three-dimensional animal visualizations, interactive audio, numeracy quizzes, adn a reward system,which are designed to help students understand numerical concept more concretely. Testing was conducted through three evaluations: a content expert review, a media expert review, and a user responses evaluation using the Usability Metric for User Experince (UMUX) method. The study participants consisted of two teachers and 15 students with intellectual disabilities as users of the learning media. The content expert review yielded a validity percentage of 92,86%, classified as highly valid, and the media expert review yielded a validity percentage of 90%, classified as highly valid. Additionally, the user response evaluation yielded a UMUX score of 84,16% which falls into the Excellent category and Grade A. The research findings indicate that three-dimensional visual-based interactive multimedia possesses excellent usability, is easy to use, and is suitable as an alternative learning medium for numeracy education for children with intellectual disabilities. This study contributes by providing a learning medium designed based on the characteristics of children with intellectual disabilities and the learning needs identified at the Cahaya Impian Masa Depan (CIMD). The developed multimedia is expected to serve as a reference for the development of interactive learning media in inclusive education as well as special education institutions.